The influence of school leadership and teacher performance on the learning achievement of middle school students - Dhidhik Eni Rustiyah; Nur Ahyani; Dessy Wardiah (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This study aims to determine and describe the influence of principal leadership and teacher performance on student achievement in SMA NegeriLubuk Raja OganKomeringUlu (OKU) District. The method used is a quantitative method. The data collection technique used was a questionnaire. The results of the study can be concluded that the test results show that the higher the effective leadership of the principal, the higher the student achievement squared the correlation coefficient between the two variables is 0.588. The square of the correlation coefficient between the two variables (r2y2) of 0.5069 can be interpreted that if other variables are not controlled, then 50.69% of the proportion of student achievement variance can be explained by the level of teacher performance. and the multiple correlation coefficient between the two independent variables with the dependent variable Ry.12 of 0.684. From the correlation coefficient, the coefficient of determination (R2) of 0.684 means that 68.40% of the proportion of student achievement variants can be explained jointly by the principal's leadership and teacher performance.